THE EFFECT OF PROJECT-BASED LEARNING ON SCIENTIFIC THINKING SKILL - Farkhan, Muhammad Robith; Maragustam, Maragustam (Universitas Islam Negeri Mataram, 2022)
Scientific thinking skill as the demand and a solution for the various diverse issues of the 21st century skills is necessarily crucial to be acquired by the students. The present research aims to investigate the effect of project-based learning on scientific thinking skills by employing a quasi-experimental design. The sample of this study consisted of 60 students, divided into 2 groups. In the experimental group, a project-based learning model was applied, while the control group implemented it through a communicative learning method. The data were collected using the instrumental test of scientific thinking skill which was carried out in both pre and post-learning. The data analysis of this study adopted paired sample t test and independent-sample t test. The results showed that 1) there was an effect of project-based learning models identified on scientific thinking skill, thus H1 was accepted while H0 was rejected, 2) there was no effect of communicative learning methods founded on scientific thinking skill, thus H0 was accepted and H1 was rejected. This research shows the effect of project-based learning models on scientific thinking skills.